The practice of management - Drucker, Peter F. (Oxford : Butterworth-Heinemann, 1999)
Providing information about the developments and place of management, this book contributes to the study of business efficiency. It is of interest to the applied economists and sociologists.
Originally published: U.S.: Harper, 1954; London: Heinemann, 1955
Winner of Global Business Book Award 1998.
Includes bibliographical references and index.
oif 11/03/15
Loan
Keywords: Management; Industrial management